2017
DOI: 10.1088/2058-9565/aa722a
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and classical resources for unitary design of open-system evolutions

Abstract: Abstract. A variety of tasks in quantum control, ranging from purification and cooling, to quantum stabilization and open-system simulation, rely on the ability to implement a target quantum channel over a specified time interval within prescribed accuracy. This can be achieved by engineering a suitable unitary dynamics of the system of interest along with its environment -which, depending on the available level of control, is fully or partly exploited as a coherent quantum controller. After formalizing a cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In particular, it has been shown that it is possible to preserve and even enhance the quantum dynamical features of a system by judiciously coupling the system to a dissipative environment. Applications of quantum reservoir engineering include amplification [8], nonreciprocal photon transmission [9,10], photon blockade [11], efficient photoinduced charge separation in solar energy conversion [12], binding of atoms [13,14], inducing phase transitions [15][16][17], implementation of quantum gates [18][19][20][21], and the generation of entangled [22][23][24][25][26][27], squeezed [28][29][30], and other exotic [31][32][33][34] quantum states.…”
mentioning
confidence: 99%
“…In particular, it has been shown that it is possible to preserve and even enhance the quantum dynamical features of a system by judiciously coupling the system to a dissipative environment. Applications of quantum reservoir engineering include amplification [8], nonreciprocal photon transmission [9,10], photon blockade [11], efficient photoinduced charge separation in solar energy conversion [12], binding of atoms [13,14], inducing phase transitions [15][16][17], implementation of quantum gates [18][19][20][21], and the generation of entangled [22][23][24][25][26][27], squeezed [28][29][30], and other exotic [31][32][33][34] quantum states.…”
mentioning
confidence: 99%
“…(a) Thermodynamical consistency restricts the structure of the open system control GKLS master equation [20,163,164,169,596]. (b) Certain control task require a change of entropy, such as reset or thermalization [52,56,166,168,227,558,559]. Tasks that do not require a change of entropy may still benefit from it, for example by reaching the target while actively cooling [316,415].…”
Section: Quantum Thermodynamicsmentioning
confidence: 99%
“…An elementary and universal task is the reset transformation. The control objective is a fast reset to a desired state with high fidelity [52,56,227,558,559]. The fidelity is restricted by the third law of thermodynamics: Very high fidelity requires infinite resources [550].…”
Section: Quantum Thermodynamicsmentioning
confidence: 99%
“…However, simulating the effect of decoherence is very hard because it originates from the interaction of a relatively small subset of qubits with a huge number of environmental degrees of freedom. The resulting dissipative dynamics on the system qubits can be computed along different lines based in general on adding to the system qubits with additional qubits modeling a (weak) coupling to the environment. Here, we show that such a quantum simulation can be performed on a 5-qubit supramolecule with tailored interactions.…”
Section: Introductionmentioning
confidence: 99%